DISINFECTION OF MUNICIPAL WATER USING SOLAR RADIATION: AN ECONOMICAL APPROACH FOR RURAL DWELLERS IN THE COASTAL REGION OF KARACHI - Ahmed, M. F.; Saleem, M. (The Nucleus, 2010)
At present acquiring safe drinking water in rural or remote areas of Pakistan is a challenging task for dwellers. Coast line of Karachi is a sporadic habitat of villages not having access to safe drinking water. Many incidents of waterborne diseases have been reported in that area and attributed to contaminated municipal water supply. Solution of the problem is disinfection however, general methods of water disinfection such as boiling, UV-lamp, ozonation and chemical additive are costly or require skilled manpower. Present study investigates the solar disinfection method to treat municipal water supply at Karachi Institute of Power Engineering (KINPOE) located at the costal belt of Karachi. Effect of exposure time, bottle material and turbidity of water on the process performance was evaluated. Model indicator bacteria total coliform (TC) was used to evaluate the solar disinfection process. Study revealed that in order to disinfect the municipal water, samples should be filled in PET transparent bottles, having turbidity below 23 NTU, and expose to solar radiation in the study area at least for one hour. Study shows that solar disinfection may provide safe drinking water meeting national and international water quality standards at minimum cost and effort in sunshine rich areas and not having access to other water purification systems.